Polypropylene material and use thereof

CN117186554BActive Publication Date: 2026-10-20TIANJIN KINGFA NEW MATERIAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311268083.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2026-10-20
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

[0003]上述皮纹外观件通常直接外露使用,这导致其随着使用时间的推移,会发生一定程度的老化,体现在制件上会出现褪色、析出、裂纹等缺陷

Benefits of technology

[0025](1)本申请通过添加含有(CH2)n结构单元(n≥5)的光稳定剂,以有效提高聚丙烯材料的耐候性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004474767910000011
    Figure BDA0004474767910000011
  • Figure BDA0004474767910000021
    Figure BDA0004474767910000021
  • Figure BDA0004474767910000071
    Figure BDA0004474767910000071
Patent Text Reader

Abstract

The application discloses a polypropylene material and application thereof, and belongs to the technical field of high polymer materials. The application adds a light stabilizer containing (CH2) n Structural units, wherein n is an integer greater than or equal to 5, to polypropylene resin, so as to effectively improve the weather resistance of the material, so that the material has a low color difference value, a high gloss retention rate and no whitening after xenon lamp accelerated aging, and is suitable for preparing automobile interior and exterior skin pattern parts, such as door panels, instrument panels, wheel arches, bumper trim panels, door exterior trim panels and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials technology, specifically relating to a polypropylene material and its applications. Background Technology

[0002] Polypropylene is widely used in the automotive industry, especially in interior and exterior trim materials, due to its excellent processing and physical properties. Common automotive interior and exterior trim materials such as door panels, dashboards, wheel arches, and bumper trim panels are designed with a leather-textured surface. Compared with smooth panels, its fine texture structure reduces the gloss of the material by increasing surface roughness, which can effectively reduce the cheap plastic feel of the parts, thereby improving the overall sensory comfort and refinement of the vehicle.

[0003] The aforementioned textured parts are typically used directly in the open, which leads to a certain degree of aging over time, manifesting as defects such as fading, precipitation, and cracking. Currently, OEMs mainly use the color difference value after accelerated aging under xenon lamps as an assessment method for the aging resistance of parts. However, the gloss retention of the part's surface and the precipitation of additives also affect the material's appearance after long-term use, yet research in this area is scarce. Summary of the Invention

[0004] Based on the deficiencies of existing technologies, the purpose of this invention is to provide a polypropylene material and its application. This polypropylene material has good weather resistance, and after accelerated aging under a xenon lamp (referring to SAEJ 2527-2004 standard), it has low color difference, high gloss retention and no whitening. Even after long-term use, it can maintain the novelty of the material and can be used to prepare leather-textured parts for automotive interior and exterior trim.

[0005] To achieve the above objectives, the present invention provides a polypropylene material comprising the following components in parts by weight:

[0006]

[0007]

[0008] Where n is an integer ≥ 5.

[0009] Carbon black absorbs ultraviolet light to prevent the polymer chains in polypropylene resin from being directly exposed to radiation, thus improving weather resistance. The aforementioned light stabilizers, containing longer alkyl segments, have good compatibility with polypropylene resin. This not only better protects the polypropylene resin but also reduces or prevents the precipitation of additives that could cause whitening, blooming, or other phenomena in the material.

[0010] Copolymer polypropylene, due to the presence of a certain amount of rubber phase (vinyl segments) in its molecular chain, exhibits good compatibility with light stabilizers containing longer alkyl segments and reduces the overall gloss of the material, thus maintaining a high gloss retention rate after xenon lamp accelerated aging. Homopolymer polypropylene, on the other hand, does not contain vinyl segments and, due to its higher crystallinity, has a higher overall gloss, making it less suitable for maintaining gloss retention after xenon lamp aging.

[0011] The aforementioned polypropylene material exhibits excellent weather resistance due to the combined effect of its components at specific concentrations. After accelerated aging under xenon lamps (referencing SAEJ 2527-2004 standard), the color difference value ΔE < 0.85, gloss retention rate > 88%, and slight or no whitening. Even after long-term use, the material maintains its novelty and is suitable for preparing leather-textured automotive interior and exterior parts, such as door panels, dashboards, wheel arches, bumper trim panels, and exterior door trim panels.

[0012] The one containing (CH2) n (CH2) in the light stabilizer of the structural unit n The structural unit is continuous (CH2). n Structural unit.

[0013] n is an integer ≥ 5, such as 5, 7, 9, or 12. In some embodiments, n is 6 to 8 to obtain better weather resistance, resulting in a lower color difference value ΔE and higher gloss retention after accelerated aging with a xenon lamp (refer to SAE J 2527 standard).

[0014] In some embodiments, the (CH2) content n The light stabilizers of the structural units include at least one of hindered amines and benzophenones.

[0015] When the carbon black particle size D50 is too small, it is prone to agglomeration, resulting in uneven local distribution and relatively weak weather resistance. When the carbon black particle size D50 is too large, its covering power decreases, leading to relatively weak weather resistance. To improve the weather resistance of polypropylene materials, in some embodiments, the carbon black particle size D50 is 14–81 nm, such as 15 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, or 80 nm. In particular, in one specific embodiment, the carbon black particle size D50 is 19.5–51 nm, such as 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, or 50 nm, further improving the weather resistance of the resulting polypropylene material. The carbon black particle size D50 is measured using the following method: test standard GB / T 19077-2016, using a laser particle size analyzer.

[0016] The rubber phase content in polypropylene resin not only affects the weather resistance of the resulting polypropylene material but also its appearance; the melt flow rate of the polypropylene resin affects the weather resistance of the resulting polypropylene material. In some embodiments, the rubber phase content in the polypropylene resin is 18wt% to 50wt% (e.g., 19wt%, 20wt%, 30wt%, 40wt%, or 50wt%), and the melt flow rate is above 8g / 10min (e.g., 8g / 10min, 10g / 10min, 15g / 10min, 20g / 10min, 25g / 10min, 30g / 10min, 35g / 10min, or 40g / 10min) under conditions of 230°C and a load of 2.16kg. By controlling the rubber phase content and melt flow rate in the polypropylene resin within the above ranges, it is beneficial to improve the weather resistance of the polypropylene material and reduce the probability of whitening. In a particular embodiment, the rubber phase content in the polypropylene resin is 25wt% to 41wt% (e.g., 25wt%, 27wt%, 30wt%, 32wt%, 35wt%, 37wt%, or 40wt%), and the melt flow rate of the polypropylene resin at 230℃ and a load of 2.16kg is above 15g / 10min (optionally 15 to 32g / 10min, such as 15g / 10min, 17g / 10min, 20g / 10min, 25g / 10min, 30g / 10min, or 32g / 10min). The resulting polypropylene material has better weather resistance and no whitening phenomenon. The method for characterizing the rubber phase content in the polypropylene resin is as follows: 1g of polymer sample is placed in 100mL of 98% n-decane and extracted at 145℃ to fully dissolve the rubber phase. After cooling to room temperature, the crystallized polypropylene component is filtered. 500mL of acetone is added to the filtrate to precipitate the dissolved rubber phase. The sample is then filtered, dried, weighed, and the weight is calculated. The same applies below. The melt flow rate of the polypropylene resin is measured according to standard GB / T 3682.2-2018 "Determination of Melt Index Mass Flow Rate and Melt Volume Flow Rate of Thermoplastic Plastics". The same applies below.

[0017] In some embodiments, the lubricant includes at least one of polysiloxane and polyethylene wax.

[0018] In some embodiments, the Fe2O3 content of the talc powder is less than 0.25 wt%, such as 0.24 wt%, 0.20 wt%, 0.16 wt%, 0.12 wt%, 0.08 wt%, 0.05 wt%, 0.03 wt%, 0.01 wt%, or 0. Fe2O3 in talc powder is an impurity that can induce degradation reactions in polypropylene, reducing its weather resistance and heat aging resistance. Therefore, it is preferable that the Fe2O3 content of the talc powder is less than 0.25 wt% to obtain better weather resistance and heat aging resistance. When the Fe2O3 content of the talc powder is less than 0.21 wt%, especially when the Fe2O3 content is 0–0.15 wt%, the weather resistance and heat aging resistance of the resulting polypropylene material are further improved. The Fe2O3 content in the talc powder can be determined by elemental analysis methods, the same below.

[0019] In some embodiments, the polypropylene resin has a mass fraction of 65% or more in the polypropylene material, such as 67%, 70%, 80%, 90%, 92%, etc.

[0020] The carbon black in the polypropylene material can be added in the form of pure carbon black or mixed with other color powders. In some embodiments, the carbon black in the polypropylene material is added in the form of mixed with other color powders, and the weight of carbon black accounts for more than 75% of the total weight of the color powders, such as 75%, 80%, 90%, 95%, 99%, etc.

[0021] In some embodiments, the antioxidant includes a primary antioxidant and a secondary antioxidant, wherein the weight ratio of the primary antioxidant to the secondary antioxidant is 3:2 to 2:3, wherein the primary antioxidant includes at least one of hindered phenols, amines, etc., and the secondary antioxidant includes at least one of medium phosphites, thioesters, etc.

[0022] In some embodiments, the preparation method of the polypropylene material includes the following steps: mixing the component raw materials, feeding them into a screw extruder for melt extrusion, granulation, and drying to obtain the polypropylene material. The screw extruder can be a twin-screw extruder, etc.; the length-to-diameter ratio of the screw extruder can be selected as 30:1-40:1; the melt extrusion conditions can be selected as follows: zone 1 temperature 100-120℃, zone 2 temperature 190-210℃, zone 3 temperature 210-230℃, zone 4 temperature 210-230℃, zone 5 temperature 210-230℃, zone 6 temperature 210-230℃, zone 7 temperature 210-230℃, zone 8 temperature 210-230℃, zone 9 temperature 210-230℃, and the main extruder speed 250-600 rpm.

[0023] This application also provides the application of the polypropylene material in automotive interior and exterior leather-textured parts, such as the manufacture of door panels, dashboards, and exterior trim panels.

[0024] Compared with the prior art, the beneficial effects of this application are as follows:

[0025] (1) This application involves adding (CH2) n Light stabilizers for structural units (n≥5) are used to effectively improve the weather resistance of polypropylene materials;

[0026] (2) The polypropylene material of this application has good weather resistance under the combined effect of the components in a specific amount. After accelerated aging with xenon lamp (refer to SAEJ 2527 standard), the color difference value ΔE < 0.85, the gloss retention rate > 88%, and no whitening is precipitated. Even after long-term use, the material can maintain its novelty and is suitable for use as automotive interior and exterior trim materials, such as for preparing automotive interior and exterior leather-textured parts, such as door panels, dashboards, wheel arches, bumper trim panels, door exterior trim panels, etc. Detailed Implementation

[0027] To better illustrate the purpose, technical solution, and advantages of this invention, the invention will be further described below with reference to specific embodiments and comparative examples. The purpose of this description is to provide a detailed understanding of the invention, not to limit its scope. All other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of this invention. Unless otherwise specified, the experimental reagents and instruments involved in the implementation of this invention are commonly used reagents and instruments.

[0028] Examples and Comparative Examples

[0029] Each embodiment and comparative example provides a polypropylene material. The composition of these polypropylene materials is shown in Tables 1 and 2. The preparation method includes the following steps: after the raw materials of each component are mixed evenly, they are added to the main feed port of a twin-screw extruder for melt extrusion, granulation and drying to obtain the corresponding polypropylene composite.

[0030] The melt extrusion conditions of the twin-screw extruder are: Zone 1 temperature 120℃, Zone 2 temperature 190℃, Zone 3 temperature 210℃, Zone 4 temperature 210℃, Zone 5 temperature 210℃, Zone 6 temperature 230℃, Zone 7 temperature 230℃, Zone 8 temperature 230℃, Zone 9 temperature 230℃, and main machine speed 350 rpm.

[0031] The length-to-diameter ratio of the twin-screw extruder is 40:1.

[0032] The component information used in the above embodiments and comparative examples is as follows:

[0033] Copolymer polypropylene resin 1: rubber phase content is 40wt%, melt flow rate is 30g / 10min, Lihe Zhixin KA30;

[0034] Copolymer polypropylene resin 2: rubber phase content is 28wt%, melt flow rate is 16g / 10min, Formosa Plastics K9017;

[0035] Copolymer polypropylene resin 3: rubber phase content is 27wt%, melt flow rate is 28g / 10min, Yanshan Petrochemical K9829H;

[0036] Copolymer polypropylene resin 4: rubber phase content is 19wt%, melt flow rate is 30g / 10min, Sinopec EP548RQ;

[0037] Copolymer polypropylene resin 5: rubber phase content is 49wt%, melt flow rate is 24g / 10min, Lihe Zhixin KA40;

[0038] Copolymer polypropylene resin 6: rubber phase content is 27wt%, melt flow rate is 10g / 10min, CNOOC Shell EP300M;

[0039] Homopolymer polypropylene resin: melt flow rate of 25g / 10min, Sinopec PPH-Y26;

[0040] Talc powder 1: 3000 mesh, Fe2O3 content 0.07%, Xinda SD-9286;

[0041] Talc powder 2: 3000 mesh, Fe2O3 content 0.14%, Tianyuan TYT-777A;

[0042] Talc powder 3: 3000 mesh, Fe2O3 content 0.20%, Xinda SD-9488;

[0043] Talc powder 4: 3000 mesh, Fe2O3 content 0.24%, Xinda SD-9679;

[0044] Carbon Black 1: Pure carbon black, particle size D50 is 20nm, Anhui Heiyu 1013F;

[0045] Carbon Black 2: Pure carbon black, particle size D50 is 25nm, Columbia PFEB;

[0046] Carbon Black 3: Pure carbon black, particle size D50 is 50nm, Cabot N550;

[0047] Carbon Black 4: Pure carbon black, particle size D50 is 15nm, Cabot 600L;

[0048] Carbon Black 5: Pure carbon black, particle size D50 is 80nm, Cabot N762;

[0049] Carbon Black 6: Contains carbon black, iron oxide red and titanium dioxide, of which carbon black has a mass fraction of 75% and a particle size D50 of 25nm. The carbon black grade is Columbia PFEB, and the iron oxide red and titanium dioxide are commercially available.

[0050] Light stabilizer 1: Hindered amines, containing (CH2) n Structural unit, n=6, Rianlong light stabilizer 944;

[0051] Light stabilizer 2: Benzophenone derivatives, containing (CH2) n Structural unit, n=7, Lianlong UV-531;

[0052] Light stabilizer 3: Hindered amines, containing (CH2) n Structural unit, n=8, light stabilizer 770;

[0053] Light stabilizer 4: Benzotriazoles, containing (CH2) n Structural unit, n=1, Rianlong light stabilizer 325;

[0054] Light stabilizer 5: Benzotriazole derivative, does not contain (CH2). n Structural unit, i.e., n=0, Rianlong light stabilizer 327;

[0055] Lubricant 1: Zhejiang Jiahua HG-600S, polysiloxane;

[0056] Lubricant 2: Honeywell 540A, a polyethylene wax;

[0057] Antioxidant: A mixture of hindered phenols and phosphites in a mass ratio of 1:1.

[0058] The melt flow rates of the above copolymer polypropylene resin and homopolymer polypropylene resin were measured according to standard GB / T 3682.2-2018 "Determination of melt flow rate and melt volume flow rate of thermoplastic plastics" under the test conditions of 230℃ and a load of 2.16kg.

[0059] Unless otherwise specified, all components and raw materials used in the embodiments and comparative examples of this application are commercially available, and the same type of components and raw materials are used in each parallel experiment.

[0060] Polypropylene materials from all embodiments and comparative examples were injection molded into standard leather-textured sheets of the same specifications and a thickness of 3 mm. These sheets were then subjected to xenon lamp aging tests, and the color value, gloss, and appearance of the leather-textured surface before and after aging were evaluated. Xenon lamp aging was performed according to SAEJ 2527-2004 conditions for 2100 hours; color values ​​were measured using a CM-2500C spectrophotometer; gloss was measured according to GB 8807-1988 at a 60° angle; the back side (glossy side) of the leather-textured sheet was observed under a magnifying glass (10x magnification), and the appearance was rated as follows:

[0061] Grade 1: Good surface, no whitening or other appearance defects.

[0062] Grade 2: Slight whitening occurs on the surface.

[0063] Grade 3: Severe precipitation, significant whitening, and blooming phenomenon.

[0064] Color difference △E = Color value E (before aging) - Color value E (after aging), Gloss retention rate (%) = Gloss (after aging) / Gloss (before aging) × 100, the test results are shown in Table 3.

[0065] Table 1

[0066]

[0067] Table 2

[0068]

[0069]

[0070] Table 3

[0071]

[0072]

[0073] As shown in Table 4, the polypropylene materials obtained in each embodiment of this application have good weather resistance. After accelerated aging under xenon lamp (referring to SAEJ 2527-2004 standard), the color difference value ΔE < 0.85, the gloss retention rate > 88%, and there is no whitening. It is suitable for preparing leather-textured parts for automotive interior and exterior trim, such as door panels, dashboards, wheel arches, bumper trim panels, and exterior door trim panels.

[0074] As can be seen from the comparison of Examples 2, 4-5 with Comparative Examples 1-2, compared to those without (CH2) n Light stabilizers or (CH2)-containing structural units n Light stabilizers with structural units but n < 5, containing (CH2) nLight stabilizers with structural units and n≥5 can enable materials to achieve better weather resistance.

[0075] Comparative Example 3 showed poor improvement in the weather resistance of the material due to insufficient light stabilizer dosage; Comparative Example 4 showed easy whitening and blooming due to excessive light stabilizer dosage.

[0076] Comparative Example 5 had poor weather resistance due to insufficient carbon black content and poor covering ability; Comparative Example 6 had poor weather resistance due to excessive carbon black content, which made it difficult to disperse evenly and resulted in defects in local distribution.

[0077] As can be seen from the comparison of Examples 2, 6-9, the particle size D50 of carbon black affects the weather resistance of the material. When the particle size D50 of carbon black is in the range of 19.5-51, the weather resistance of the obtained material is better. However, when the particle size D50 of carbon black is low, such as 15 nm, the particles are too small and are prone to agglomeration, resulting in uneven local distribution of carbon black and relatively poor weather resistance of the material. When the particle size D50 of carbon black is high, such as 80 nm, the large particle size leads to a decrease in the covering ability, resulting in poor weather resistance of the material.

[0078] Examples 2 and 11-15 show that the rubber content of polypropylene resin affects the weather resistance of the material. When the content is in the range of 25wt% to 41wt%, the resulting material has better weather resistance. However, when the content is low, such as 25wt%, the low content of polyethylene segments leads to relatively poor compatibility with the light stabilizer, resulting in relatively poor weather resistance. When the content is high, such as 49wt%, the excessive rubber phase content easily causes phase separation, resulting in uneven distribution of the rubber phase and crystalline phase additives, leading to relatively poor appearance and weather resistance. In addition, the melt flow rate of polypropylene resin also affects the weather resistance of the material. When the melt flow rate of polypropylene resin is low, such as 10g / 10min, the poor fluidity makes it easy for the light stabilizer to be unevenly distributed in various parts of the molded part, which also leads to poor weather resistance. Therefore, the melt flow rate of polypropylene resin is preferably in the range of 15-32g / 10min.

[0079] As can be seen from the comparison of Examples 2, 16-18, the Fe2O3 content in talc powder affects the weather resistance of the material. When the Fe2O3 content in talc powder is high, such as 0.24wt%, Fe2O3 induces polypropylene degradation more significantly, resulting in poor weather resistance and heat aging resistance of the material. Therefore, it is preferable that the Fe2O3 content in talc powder is less than 0.21wt%.

[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A polypropylene material, characterized in that, It includes the following components in parts by weight: 69-75 parts copolymer polypropylene resin, 20-31 parts talc, 1-2.2 parts carbon black, 0.6-0.83 parts antioxidant, and contains (CH2). n The structural unit contains 0.3-0.62 parts of light stabilizer and 0.3-0.62 parts of lubricant. Where n is an integer ≥ 5; The particle size D50 of the carbon black is 20~50nm; The copolymer polypropylene resin has a rubber phase content of 27wt%~40wt%, and a melt flow rate of 16~30g / 10min at 230℃ and a load of 2.16kg. The one containing (CH2) n The light stabilizer of the structural unit is at least one of light stabilizer 944, light stabilizer UV-531, and light stabilizer 770; the Fe2O3 content of the talc is less than 0.2 wt%.

2. The polypropylene material as described in claim 1, characterized in that, The lubricant includes at least one of polysiloxane and polyethylene wax.

3. The polypropylene material as described in claim 1, characterized in that, The Fe2O3 content of the talc is 0~0.15wt%.

4. The polypropylene material as described in claim 1, characterized in that, The antioxidant includes a primary antioxidant and a secondary antioxidant, wherein the weight ratio of the primary antioxidant to the secondary antioxidant is 3:2 to 2:

3. The primary antioxidant includes at least one of hindered phenols and amines, and the secondary antioxidant includes at least one of medium phosphites and thioesters.

5. The application of the polypropylene material as described in any one of claims 1 to 4 in the preparation of leather-textured automotive interior and exterior parts.

Citation Information

Patent Citations

  • High-blue-phase high-heat-resistance polypropylene composition as well as preparation method and application thereof

    CN113583341A

  • Fragrant heat-aging-resistant scratch-resistant polypropylene material and preparation method thereof

    CN114479335A